Fiscal consolidation in Germany - Werner Roeger; Jan in't Veld; Lukas Vogel (Intereconomics, 2010)
The German federal government's fiscal consolidation package, announced in June, is designed to permanently reduce the federal deficit to a new target level. This article uses a three-region version of the European Commission's QUEST model to gauge the impact of the package on Germany and the spillover to the rest of the euro area and the rest of the world.
Keywords: 330